ANALYSIS OF HUMAN RESOURCE COMPETENCIES AND UTILIZATION OF INFORMATION TECHNOLOGY ON THE WORK PRODUCTIVITY OF BUSINESS - Malikhah, Ikhah; Nasution, Anggi Pratama; Kaban, Gita Pratiwi (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2023)
The rapid development of information technology has made almost all business actors open their eyes by paying attention to the development of information technology in order to be able to compete in a competitive, effective and efficient manner. This study aims to analyze the effect of human resource competence and the use of information technology on the work productivity of business actors in Pematang Serai Village, Tanjung Pura District, Langkat Regency. Models and data analysis techniques in this study used a multiple linear regression approach using a questionnaire research instrument. The sample for this study was 57 respondents including: micro, small and medium enterprises in Pematang Serai Village using a questionnaire to collect data. The results of hypothesis testing indicate that competence and utilization of information technology have a partial and simultaneous positive and significant effect on work productivity. The results of the test for the coefficient of determination explain that the determination of the independent variables of competence and utilization of information technology on the dependent variable of work productivity is 22%, while the remaining value is 78% which can be explained by other independent variables.